All Days 2014
DOI: 10.2523/iptc-17264-ms
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Gas-Condensate Relative Permeability

Abstract: When the pressure in a gas condensate reservoir falls below the dew point, liquid condensate can accumulate in the pore space of the rock. This can reduce well deliverability and potentially affect the compositions of the produced fluids. Forecasting these effects requires relative permeability data for gas-condensate flow in the rock in the presence of immobile water saturation. In this study, relative permeability measurements have been conducted on reservoir rock at a variety of conditions. The goal has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The fourth region is the closest to the wellbore, the velocity of gas flow is really high, and the liquid phase saturation is decreased through gas velocity stripping (Fevang and Whitson, 1996). To accurately understand the effect of the present of condensate bank on fluid flow, Kalla et al (2015) showed the experimental measurements of the relative permeability of different rock-fluid properties. In their results, the maximum relative permeability of condensate phase is below 0.4, which indicates a relative low conductivity of the liquid phase in condensate reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth region is the closest to the wellbore, the velocity of gas flow is really high, and the liquid phase saturation is decreased through gas velocity stripping (Fevang and Whitson, 1996). To accurately understand the effect of the present of condensate bank on fluid flow, Kalla et al (2015) showed the experimental measurements of the relative permeability of different rock-fluid properties. In their results, the maximum relative permeability of condensate phase is below 0.4, which indicates a relative low conductivity of the liquid phase in condensate reservoirs.…”
Section: Introductionmentioning
confidence: 99%